The Effectiveness of Learning Management Systems in Enhancing Student Learning Outcomes in Higher Education - Supriadi, Supriadi; Pahrudin, Agus; Yuberti, Yuberti; Rinaldi, Achi (Jurnal Ilmiah Iqra', 2025)
The rapid digital transformation in education has brought significant challenges and opportunities, particularly in integrating technology to improve learning outcomes. This study aims to analyze the effectiveness of Learning Management Systems (LMS) in enhancing student learning outcomes, focusing on the Education Management course. Using a quasi-experimental design, the research involved 18 students who underwent pre-test and post-test assessments. The results showed a significant improvement in learning outcomes, with the average post-test score (80.67) significantly higher than the pre-test score (54.89), supported by statistical analysis (sig. 0.000). The findings align with Al-Fraihat et al. (2020) and Sun et al. (2008), emphasizing the importance of LMS usability, content quality, and integration with active learning strategies. However, challenges such as the digital divide and lack of face-to-face interaction need addressing through equitable access to technology and hybrid learning models. The study concludes that LMS is an effective tool for digital learning transformation, recommending continuous content development, training, and periodic evaluation to maximize its potential.